REVISITING THE LINKAGE BETWEEN DOMESTIC SAVINGS AND ECONOMIC GROWTH IN NIGERIA - Joseph Olorunfemi AKANDE (Association of Social and Educational Innovation, 2024)
In general, economic growth that is generated by domestic savings is more sustainable than growth that is generated by debt. Sequel to this, this study revisits the linkage between domestic savings and economic growth in Nigeria. Data obtained from World Development Indicator (WDI, 2022) is used in the study. Essentially, the study employed VECM and Granger causality test to evaluate the linkage amid employed variables. The findings of the study reveal that interest rate and economic growth are essentially inversely related. However, the causal relationship between FDI and economic growth is one-sided. Furthermore, interest rate granger causes economic growth. Thus, this study concludes that, on the one hand, domestic savings in Nigeria have a positive and considerable impact on economic growth, while, FDI is a critical component that drives domestic savings in Nigeria. This study recommends that policymakers to implement a favorable monetary policy that will encourage increases in the amount of money in circulation, interest rates, exchange rates, and lending to the private sector in the direction of economic growth.